PERKAWINAN CAMPURAN PADA MASYARAKAT ADAT PAPUA DAN PAPUA NEW GUINEA - Marina, Liza; Sunarsi, Dessy (MAJALAH ILMIAH WIDYA, 2012)
Many Indonesian citizen in Papua who perform marriages with citizens of Papua New Guinea (PNG), particularly in border areasrdefers to the Adat marriage law. In national law, it means mixed marriages between Indonesian citizens with foreign nationals. Theproblems arise if the husband and wife in that marriage are finally divorced. The purpose of this paper is to discuss the marriagecustoms in the land border between Indonesia and other countries with different problems which take a study case of mixed marriagesbetween indigenous Papuans and Papua New Guinean. The method of writing is through literature study which is taken are from AdatMarriage Law and Private International Law references. The conclusions are: (1) In Papua marriage Adat law, when the marriage isdivorce, the guidelines refers to manner of the marriage couples during the marriage and who makes mistakes. (2) The marriagedispute is overcome by Adat law at the right side village. (3) If the guilty side is the wife, so the wife must return the number of dowryand pay the fines.